2019
DOI: 10.1016/j.neuroscience.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Priming as Trained Immunity in the Brain

Abstract: In this review we discuss the possibility that the phenomenon of microglial priming can be explained by the mechanisms that underlie trained immunity. The latter involves the enhancement of inflammatory responses by epigenetic mechanisms that are mobilized after first exposure to an inflammatory stimulus. These mechanisms include long-lasting histone modifications, including H3K4me1 deposition at latent enhancer regions. Although such changes may be beneficial in peripheral infectious disease, in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 68 publications
(118 reference statements)
2
76
0
Order By: Relevance
“…Long-lived tissue-resident macrophages are present in many tissues and show distinct enhancer landscapes that are shaped by the local tissue environment. 70,71 Microglial cells, which are the brain-resident macrophages, have also been described to exhibit an exaggerated inflammatory response upon a secondary stimulation, which has been termed microglial priming, although Haley et al 72 recently suggested that mechanistically, microglial priming should be considered a form of trained immunity. Microglial priming was suggested to underlie the observation that chronic or repeated systemic injection with LPS activates microglial cells that then give an exaggerated inflammatory response when challenged locally with LPS.…”
Section: Microbiome and Innate Memorymentioning
confidence: 99%
“…Long-lived tissue-resident macrophages are present in many tissues and show distinct enhancer landscapes that are shaped by the local tissue environment. 70,71 Microglial cells, which are the brain-resident macrophages, have also been described to exhibit an exaggerated inflammatory response upon a secondary stimulation, which has been termed microglial priming, although Haley et al 72 recently suggested that mechanistically, microglial priming should be considered a form of trained immunity. Microglial priming was suggested to underlie the observation that chronic or repeated systemic injection with LPS activates microglial cells that then give an exaggerated inflammatory response when challenged locally with LPS.…”
Section: Microbiome and Innate Memorymentioning
confidence: 99%
“…In the periphery, the priming response is mediated by permissive epigenetic modifications of latent enhancers in the promoters of pro-inflammatory genes, resulting in greater expression upon second exposure. Microglia are innate immune cells and are known to be activated following exposure to pathogens or toxins, leading to the suggestion that this is also a case of priming [43]. The priming response can last for weeks to months, meaning the majority of the lifetime of a mouse.…”
Section: Microglial Priming As a Source Of Immune Memorymentioning
confidence: 99%
“…Permanent changes in neuroimmune function have been observed after prenatal or early life immune challenge in and effect termed “microglia priming.” Here maternal immune challenge during pregnancy or early life immune challenge result in increased responsiveness of microglia to immune challenge during adulthood (Schwarz and Bilbo, 2012; Bilbo, 2013; Haley et al, 2017). More recently, several studies demonstrate similar priming effects after immune challenge in adults, with changes in microglial and astrocytic function and behavior (Fenn et al, 2014; Norden et al, 2015; Muccigrosso et al, 2016; Liddelow and Barres, 2017; Olivieri et al, 2018; Wendeln et al, 2018).…”
Section: Persistent Changes In Brain State After Immune Challengementioning
confidence: 99%
“…In the periphery, methylation of histone H3 mediates increased innate immune responses (Kleinnijenhuis et al, 2012). Similarly, in the brain, acetylation and methylation of H3 are associated with altered astrocyte and microglial function after immune challenge (Schaafsma et al, 2015; Haley et al, 2017; Wendeln et al, 2018). Together, these findings demonstrate that a prior immune challenge causes persistent changes in neuroimmune function, or neuroimmune “training,” and results in vulnerability to later immune events.…”
Section: Persistent Changes In Brain State After Immune Challengementioning
confidence: 99%